Decadal advances and future prospects in subunit vaccine development against Streptococcus suis infection - Fang, Lihua; Ning, Jie (Frontiers in Immunology, 2025)
Streptococcus suis (SS), particularly serotype 2 (SS2), is a significant zoonotic pathogen causing severe disease in swine and humans. High genetic diversity and antibiotic resistance complicate vaccine development. We firstly synthesize the pivotal advances in SS subunit vaccine design over the past ten years, thereby establishing a foundation for guiding future rational vaccine development. Promising candidates, including pS-Lpp-SaoA (delivered via OMVs), SaoA (via live vectors), IgA1 protease, rIde-10, rIde-14009-1, Enolase, 6-GPD, 38-BP-Enol, and multi-antigen formulations (MRP/GAPDH/DLD or SLY/Enolase/Sbp), elicit robust immune responses (high IgG/IgA titers) and confer up to 100% protection against lethal SS2 challenge in murine and porcine models. Cross-protection against heterologous serotypes (e.g., SaoA and Enolase delivered via S. Choleraesuis) is observed. Future efforts should prioritize: discovery of conserved antigens, optimization of delivery platforms/adjuvants, and translational validation in pigs to achieve broad, durable immunity.